Efektivitas Strategi Micro Teaching Berbasis 4S terhadap Kualitas Dokumentasi Keperawatan - Utomo, Budi; Murdiati, Fransisca Sri; Prasetyo, Joko; Nyoto, Nyoto (Kolaborasi: Jurnal Pengabdian Masyarakat, 2026)
Introduction: Nursing documentation quality remains a critical challenge in Indonesian hospitals, with inconsistencies in the application of standardized terminology (SDKI, SLKI, SIKI, and SPO) affecting clinical decision-making, patient safety, and continuity of care. Microteaching, as an evidence-based pedagogical approach, offers promise for developing nursing competencies through structured practice-feedback cycles. However, few studies have evaluated microteaching combined with 4S framework content specifically for nursing staff in clinical settings. Objective: This community service initiative aimed to evaluate the effectiveness of microteaching-based 4S intervention in improving nursing documentation quality in Asoka Ward, Bhayangkara RS H.S. Samsoeri Mertojoso Surabaya. Method: An educational intervention was designed integrating microteaching principles with 4S standardized nursing terminology. The program involved 32 nursing staff across three implementation cycles over September–October 2025. Data were collected through pre- and post-intervention assessments of documentation completeness, accuracy of diagnosis-outcome-intervention linkage, timeliness of documentation, and knowledge retention using structured instruments aligned with PPNI standards. Result: Post-intervention documentation quality showed significant improvements: diagnostic accuracy increased 24.3%, outcome specification improved 28.1%, intervention-diagnosis linkage improved 31.7%, and documentation timeliness (completion within 8 hours) increased from 34% to 78% compliance. Knowledge retention assessed through reflection-based performance rubrics showed sustained understanding in 87.5% of participants at 4-week follow-up. Conclusion: Microteaching-based 4S intervention proved effective in strengthening nursing staff competency in clinical documentation. This evidence-based approach demonstrates feasibility for replication across Indonesia’s teaching hospitals and supports quality improvement initiatives aligned with national nursing standards and accreditation requirements.